REVIEW ARTICLE: TERAPI FARMAKOLOGI MENINGITIS TUBERKULOSIS - Adira Rahmawaty (Jurnal Health Sains, 2023)
Tuberculosis Meningitis is a type of extrapulmonary TB that is very deadly because it infects the central nervous system. Therefore post-diagnosis pharmacological therapy is needed to maintain and improve the quality of life of patients. Based on this, there were 210 articles related to keywords and 15 articles that met the inclusion criteria. The main pharmacological therapies for patients with tuberculous meningitis include rifampicin, isoniazid, pyrazinamide, ethambutol, dexamethasone, and third-class cephalosporin antibiotics.